1997
DOI: 10.1118/1.598125
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of photon and electron beams with an extrapolation chamber

Abstract: This manuscript has been reproduced trom the microfilm master. UMI films the text directly trom the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face. white others may be trom any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct prim, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reprodudion.ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Earlier reports by Klevenhagen[8] and Zankowski and Podgorsak[910] have brought out the possibility of using such designed prototype versions of extrapolation chambers for the estimation of the absorbed dose from clinical linacs and tele-cobalt beams. These authors have used polystyrene and solid water phantoms for the construction of extrapolation chambers, and measured absorbed doses at selected depths in tissue-equivalent media.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier reports by Klevenhagen[8] and Zankowski and Podgorsak[910] have brought out the possibility of using such designed prototype versions of extrapolation chambers for the estimation of the absorbed dose from clinical linacs and tele-cobalt beams. These authors have used polystyrene and solid water phantoms for the construction of extrapolation chambers, and measured absorbed doses at selected depths in tissue-equivalent media.…”
Section: Discussionmentioning
confidence: 99%
“…The charge in nC, corresponding to 1.5mm plate separation, is used for calculation of the absorbed dose (based on the recommendation of Zankowski and Podgorsak,[10] suggesting 1 to 2mm as the true Bragg-Gray region for the EC). Recombination correction is carried out by using the standard two voltage technique +400V and +200V.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…92,93 It is often implied or suggested that the extrapolated zero volume ionization ratio (PDI) gives the PDD. 87,90,94 In fact the extrapolated zero volume ionization gives the true ionization that would have occurred if there were no perturbation effects. The change in stopping power ratio from the surface to depth of maximum dose still remains a source of uncertainty in converting PDI to PDD even with an extrapolation chamber.…”
Section: B2 Detectors Used For Measurement Of Surface Dose and Bumentioning
confidence: 99%